Uncertainty handling in containerized logistics: Unitary Traceability Object approach - S. Wattanakul (2020)
© 2019 IEEE. The transit time of transportation and port clearance is considered as the second most salient risk in the global supply chain. This further affects the accurate estimation of shipment lead time due to the high variability. This research proposes a literature review to explore the behaviour of uncertainty influencing the global logistics chain. The classification of logistics roles (Shipper, Shipping line, Port: Fundamental and Port: Intermodal) presents how the uncertainty currently influences the decisions of each logistics role in strategical, tactical and operational problems. It is found that uncertainty occurred during the logistics operation influencing to all logistics roles and it is transferrable to the adjacent logistics role. The Unitary Traceability Object such as smart container has an opportunity to monitor the logistics operation and extract the behaviour of uncertainty during the operation in the field. This information further supports the planning decisions to respond/treat the uncertainty.